Body Mass Index and Prognosis in Ischemic Stroke Patients With Type 2 Diabetes Mellitus - Park, Hyungjong; Lee, Hyung Woo; Yoo, Joonsang; Lee, Hye Sun; Nam, Hyo Suk; Kim, Young Dae; Heo, Ji Hoe (Frontiers in Neurology, 2019)
Overweight contributes to type 2 diabetes mellitus (T2DM) development. Although the obesity paradox has been suggested in many vascular diseases, little information is available about stroke patients with T2DM. We investigated whether body mass index (BMI) has a differential impact on the incidence of major adverse cardiovascular events (MACE) in patients with ischemic stroke and T2DM. Methods: This retrospective study used a prospective cohort of patients with acute ischemic stroke, and included consecutive patients with T2DM after excluding those with active cancer or who died within 1 month of an index stroke. We investigated the long-term risk of MACE (stroke, myocardial infarction, unstable angina, coronary revascularization procedure, and death) according to BMI. Results: Among the 1338 patients, MACE occurred in 415 patients (31.1%) during a median follow-up of 3.6 years. Compared to the normal weight group, MACE occurred more frequently in the underweight group (adjusted hazard ratio [HR] 1.55, 95% confidence interval [CI] 1.01-2.38), but less frequently in the overweight group (adjusted HR 0.87, 95% CI: 0.70-1.08) and obese group (adjusted HR 0.58, 95% CI 0.41-0.86) group. In analyses of association between BMI and each component of MACE, stroke and cardiovascular mortality indicated an L- and a U-shaped pattern, respectively. However, fatal or non-fatal stroke showed an inverse pattern, and fatal or non-fatal cardiovascular events showed a reversed J-shaped pattern. Discussions: This study showed the overall presence of the obesity paradox in stroke patients with T2DM. However, obese patients had different risks of cardiovascular events and stroke.